Molecular analysis of Helicobacter pylori virulent-associated genes in hepatobiliary patients - Boonyanugomol, Wongwarut (Blackwell Publishing Ltd, 2012)
OBJECTIVES: The Helicobacter pylori virulence-associated genes in hepatobiliary patients, including vacA, iceA, babA2, cagA and cagE, have not been reported. The aim of this study was to investigate these genes and the association of those and the clinical outcomes in hepatobiliary diseases. METHODS: Eighty H. pylori-PCR-positive cases were obtained from hepatobiliary patients, representing both cholangiocarcinoma (CCA) (n = 58) and cholelithiasis (n = 22). The diversity of virulence genes was examined by polymerase chain reaction and DNA sequencing. Phylogenetic analysis of cagA was determined using the maximum parsimony method. RESULTS: The vacAs1a + c/m1, iceA1 and babA2 genes were the most predominant genotypes in both CCA and cholelithiasis patients. The cagA and cagE genes were found significantly more frequently in patients with CCA than those with cholelithiasis (P < 0.05). The cagA positive samples were the Western-type cagA and showed that almost all of the detected sequences in Thai hepatobiliary and Thai gastric cancer patients were classified in the same cluster but separated from the cluster of Japan and other countries. CONCLUSIONS: The cagA and cagE genes may be associated in the pathogenesis of hepatobiliary diseases, especially of CCA. Besides the bacterial variation, other host factors may be involved in the pathogenesis of hepatobiliary cancer.